Construcciones impersonales con se en espanol y su tratamiento didáctico desde una perspectiva de focus on form o la atención a la forma - Trenc, Andreja (Vestnik za tuje jezike, 2012)
The article deals with the input processing methodology potential (VanPatten, 1996), based on the principles of the Cognitive Grammar and focus on form oriented instruction as an alternative approach to understanding and teaching impersonal syntax structures with clitic se and other complex syntax features of the Spanish Language. Explicit grammar instruction involving student's active processing of the input is considered in this investigation as a plausible approach to a better and more straightforward acquisition of formal grammatical features, reducing positively the cuantity of the common mistakes in the process of the acquisition within the advanced learners of Spanish (such as Slovene Graduate Students in the Hispanic Linguistics, assigned to take part in this investigation). Applying the empiric means of research based on the model of the custom-made input processing grammar activities, the article sets out a number of arguments in favour of a major didactic value and teachability of the described methodology: (1) its consonance with the universal cognitive processes activated during the acquisition, (2) a better adequacy to meeting student's cognitive needs, (3) an alternative for improving the ways complex sintactic forms in Spanish have been dealt with up till now on Advanced Levels and, lastly, (4) its compatibility with the contemporary methods and trends in Didactics of Spanish Grammar, such as communicative approach and student-centred learning.
Keywords: Spanish; španščina; tuji jeziki; grammar; slovnica; kognitivna slovnica; neosebne skladenjske strukture; morfem "se"; didactic method; didaktika; metodika